2007
DOI: 10.1002/art.22379
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab for long‐term treatment of psoriatic arthritis: Forty‐eight week data from the adalimumab effectiveness in psoriatic arthritis trial

Abstract: Objective. To evaluate the efficacy and safety of treatment with adalimumab, a fully human anti-tumor necrosis factor (anti-TNF) monoclonal antibody, over 48 weeks in patients with moderate to severe psoriatic arthritis (PsA).Methods. Patients who completed the Adalimumab Effectiveness in Psoriatic Arthritis Trial (ADEPT), a 24-week, double-blind study of adalimumab versus placebo in PsA, could elect to receive open-label adalimumab, 40 mg subcutaneously every other week after week 24. Radiographs were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
186
1
13

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 265 publications
(206 citation statements)
references
References 34 publications
6
186
1
13
Order By: Relevance
“…Safety findings through week 52 were consistent with week-24 results (6) and with those for other biologic agents, including anti-TNF agents, in PsA (19)(20)(21)(22)(23). The proportion of patients with Ն1 AE was ϳ78% overall and tended to be higher with longer duration of followup.…”
Section: Discussionsupporting
confidence: 78%
“…Safety findings through week 52 were consistent with week-24 results (6) and with those for other biologic agents, including anti-TNF agents, in PsA (19)(20)(21)(22)(23). The proportion of patients with Ն1 AE was ϳ78% overall and tended to be higher with longer duration of followup.…”
Section: Discussionsupporting
confidence: 78%
“…Because PsA is a co-morbidity of psoriasis, patients with psoriasis should be screened for the presence of PsA, since early detection and aggressive treatment appear to prevent joint damage. [123][124][125] Patients with psoriasis should be monitored for the development of PsA.…”
Section: Recommendationsmentioning
confidence: 99%
“…A recent report showed that ADA improved joint and skin manifestations, reduced disability, and inhibited radiographic progression over 48 weeks in patients with PsA who were participants in ADEPT. ADA was well tolerated through week 48 and MTX use at baseline was not required for clinical or radiographic efficacy [24].…”
Section: Adamentioning
confidence: 99%